ANALYSIS OF TIPPING BEHAVIOUR TOWARDS ONLINE TRANSPORTATION SERVICE PARTNER BEFORE AND DURING COVID-19 OUTBREAK - Muhammad Ahmi Husein; G. Oka Warmana (STIE Mahardhika, 2022)
Online Transportation Services are growing significantly in Indonesia from 2015 to 2020. With their proposed value propositions, this service has become one of the most popular services in Indonesia. Due to the high customer satisfaction of this service, many customers give tips to the driver or riders as a reward for the service. However, since the COVID-19 outbreak in Indonesia, the user traffic of this service has been decreasing significantly. As a result, many partners of this service cannot earn adequate income for their families. In response to this, to help alleviate the life of these service partners during the COVID-19 outbreak, a campaign has been started through social media to encourage customers to give more tips to these service partners. Based on this phenomenon background, this study was conducted to analyse the customer tipping behaviour change on this service before and during the COVID-19 outbreak in South Sulawesi and South East Sulawesi province. Wilcoxon Signed-Rank Test Analysis Method was used to analyse 74 respondent data. There are eight customer categories in this study. The results show significant changes in the tip size for Customers with No Income and Customers from South East Sulawesi category. Another interesting finding is that although most respondent customers as a mean to reward the service, the number of customers who give a tip for almsgiving is increasing significantly during the COVID-19 outbreak.